Evaluating Disaster Damages and Operational Status of Health-Care Facilities During the Emergency Response Phase of Hurricane Maria in Puerto Rico. (February 2020) - Irvin-Barnwell, E.A.; Cruz, M.; Maniglier-Poulet, C.; Cabrera, J.; Rivera Diaz, J.; De La Cruz Perez, R.; Forrester, C.; Shumate, A.; Mutter, J.; Graziano, L.; Rivera Gonzalez, L.; Malilay, J.; et al.
ABSTRACT: On September 20, 2017, Hurricane Maria made landfall on Puerto Rico as a category 4 storm, resulting in serious widespread impact across the island, including communication and power outages, water systems impairment, and damage to life-saving infrastructure. In collaboration with the Puerto Rico Department of Health, the Public Health Branch (PHB), operating under the Department of Health and Human Services Incident Response Coordination Team, was tasked with completing assessments of health-care facilities in Puerto Rico to determine infrastructure capabilities and post-hurricane capacity. Additionally, in response to significant data entry and presentation needs, the PHB leadership worked with the Puerto Rico Planning Board to develop and test a new app-based infrastructure capacity assessment tool. Assessments of hospitals were initiated September 28, 2017, and completed November 10, 2017 ( n = 64 hospitals, 97%). Assessments of health-care centers were initiated on October 7, 2017, with 186 health-care centers (87%) assessed through November 18, 2017. All hospitals had working communications; however, 9% ( n = 17) of health-care centers reported no communication capabilities. For the health-care centers, 114 (61%) reported they were operational but had sustainment needs. In conclusion, health-care facility assessments indicated structural damage issues and operational capacity decreases, while health-care centers reported loss of communication capabilities post-Hurricane Maria.